Early prenatal diagnosis of conjoined twins: a case report - Cunha, Soraia S.; Coutada, Rosália S.; Neiva, Ana R.; Nogueira, Rosete (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Conjoined twins are a very rare complication of monochorionic monoamniotic pregnancies, associated with severe mortality and morbidity. Ultrasonography has made early diagnosis of conjoined twins possible, allowing prompt management and counselling of parents. The diagnosis should be suspected when monozygotic fetuses are shown to consistently hold the same fixed position relative to each other. The location and extent of fusion between the twins determine the potential for surgical separation and postnatal survival. The authors report a case of conjoined thoraco-omphalopagus twins, diagnosed by ultrasonography at 10 weeks of gestation. Due to high complexity of fetal fusion, termination of pregnancy was performed upon patient´s request.